Implementasi Nilai-nilai Pendidikan Agama Islam dalam Mengembangkan Empati Sosial dan Stabilitas Emosi Remaja - Neneng Nurhasanah; Iis Basyiroh; M Mahbub Al Basyari; Maslukah (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
In this fast-paced modern era, the social and emotional development of teenagers is a big challenge, especially with the negative influence of technology and the social environment. Islamic Religious Education (PAI) in schools can play an important role in shaping students' social and emotional character. This research aims to examine the role of PAI in developing social empathy and emotional stability in adolescents at SMPIT Buah Hati. The research method used is a qualitative descriptive method with a case study approach. Data was collected through observation, interviews with teachers and students, and documentation. The data analysis technique uses descriptive analysis to describe changes that occur before and after implementing the PAI program. The research results showed that the implementation of the PAI program was successful in increasing students' abilities in listening to friends' feelings, showing social concern, managing emotions, and resolving conflicts. Significantly, students also participate more actively in social activities. The implications of this research show that religious education based on the values of social empathy can form a character that is more stable and caring towards others. However, external challenges such as the influence of social media need to be taken into account, so support from family and community is very necessary to optimize student character development. This research contributes to strengthening understanding of the importance of religious education in forming the social and emotional character of adolescents at school.